Operationalizing Deep Structural Sustainability in Business: Longitudinal Immersion as Extensive Engaged Scholarship. (January 2017) - Wells, Peter; Nieuwenhuis, Paul
Abstract : This paper offers an innovative perspective on engaged scholarship as multiple, cumulative interactions between academia and external organizations in the business and policy realms. A definition of longitudinal immersion is positioned relative to the extant literature on academic engagement as a dialectic relationship between academic research and the praxis of business and society. Using a case study of a specific academic theoretical concept, we seek to demonstrate how over a period of some 25 years the ideas and practice of deep structural sustainability have co‐evolved through a process of reflexivity. Drawing from critical management studies and design science we give a different perspective on the processes and mechanisms of engagement and the question of the nature of impact. Notwithstanding the challenges thus presented to researchers in nurturing the ability for informed creativity, it is concluded that future opportunities for engagement and impact may be captured by a longer‐term, value‐driven and less episodic approach to the entire research process.